Analisa Analisa Kelelahan Dan Kekerasan Pada Logam Axle shaft Dengan Pengelasan Gesek - muhammad faisal; Asrul Asrul (Politeknik Negeri Padang, 2022)
The axle shaft is a component of the power transfer system which often experiences mechanical failure. The purpose of this study was to determine the degree of fatigue and hardness of metal shafts with variations in frictional load as information on friction welding recommendations on metal shafts. The research method used is the experimental method, which is a way to compare specimens with variations in friction welding loads of 2 kg, 4 kg, and 6 kg using the Rockwell method of hardness testing and fatigue testing using a rotary bending machine. From the research results it is recommended that friction welding on metal axle shafts can be carried out with a friction load of 6 kg because from the results of the fatigue test SPBG6 has the highest average fatigue strength compared to SPBG2 and SPBG4. This was reinforced by the results of the SPBG6 hardness test which showed the lowest hardness level for the parent metal at 80.44 HRA.